2016
DOI: 10.1007/s00167-016-4189-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of electronic administration of knee surveys among ACL-injured patients

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Patient‐reported outcomes measures were completed either in person (pen and paper) or via the online portal PROmptus–Medical (DS PRIMA) with instructions matching the original paper version. The KOOS (intraclass correlation coefficient [ICC] >0.96) and IKDC (ICC 0.79) questionnaires have demonstrated test–retest reliability between paper and electronic formats.…”
Section: Methodsmentioning
confidence: 99%
“…Patient‐reported outcomes measures were completed either in person (pen and paper) or via the online portal PROmptus–Medical (DS PRIMA) with instructions matching the original paper version. The KOOS (intraclass correlation coefficient [ICC] >0.96) and IKDC (ICC 0.79) questionnaires have demonstrated test–retest reliability between paper and electronic formats.…”
Section: Methodsmentioning
confidence: 99%
“…Authors reported good agreement between the 2 MOA for the Tegner and Marx activity scales, Lysholm Knee Scale, and the International Knee Documentation Committee, with ICCs ranging from .65 to .79. 3 The agreement between digital and paper MOA has also been established in patients with rheumatoid arthritis. It was found that a digitally delivered version of the Patient Global Assessment of Disease Activity, the Global Health score, and a visual analog scale had ICCs above .95 for all 3 measures.…”
Section: Discussionmentioning
confidence: 90%
“…2 Similar results have been reported in patients with rheumatoid arthritis and anterior cruciate ligament injury. 3,4 Together, the research suggests that for musculoskeletal conditions, the time and cost benefits of using a digital MOA do not result in a trade-off to the psychometric properties of PROs.…”
mentioning
confidence: 95%
“…We recommend that work with key stakeholders including surgeons, therapists, and patients and their carers is needed to ensure that the measure is appropriate and can be effectively used across different conditions. Key design features will include ease of use and digital solutions, as electronic patientreported outcomes have been shown to be useful in similar patient groups [44].…”
Section: Discussionmentioning
confidence: 99%